Applying the International Classification of Functioning–Children and Youth Version to Pediatric Neuro-oncology. (January 2017) - Pletschko, Thomas; Felnhofer, Anna; Schwarzinger, Agathe; Weiler, Liesa; Slavc, Irene; Leiss, Ulrike
Given the increased survival rates in patients with pediatric central nervous system tumors, late effects such as treatment- and/or illness-related neurologic sequelae as well as neuropsychological deficits and social difficulties have moved into focus in follow-up care. In order to provide personalized treatment recommendations for pediatric brain tumor survivors, it is crucial not only to assess cognitive impairments but also to measure a patient's functional deficiencies, for example, restricted participation in everyday social activities. Thus, this article introduces the International Classification of Functioning–Children and Youth version (ICF-CY) as a conceptual framework for quantifying functional limitations and informing long-term care in pediatric neuro-oncology. A standardized self-report and proxy-report questionnaire for measuring participation is briefly discussed and specific recommendations based on so-called core sets for clinical practice in pediatric neuro-oncology are provided.